Chapter Structure and dynamics of immigration in the municipalities of northwestern Italy - Ballabio, Simona (Proceedings e report, 2023)
The variability of the characteristics of immigration at different territorial levels is an important key to interpreting social phenomena. This paper deals with immigration in the municipalities of the Northwest of the country. In the analysis, the databases of official statistics are considered. In particular, foreign population incidences based on ISTAT data in the last decades are used. The approach is a mix of complementary techniques of spatial analysis, known in the literature: the Univariate local Moran's Index, the Differential local Moran's Index and the LISA Cluster Transitions technique. The combined use of these tools allows both the representation of immigration structure at the municipal level and the analysis of its spatial dynamics. The results, determined by the complementarity of different methods of spatial analysis, allow to identify clusters of municipalities and to understand both differences and the dynamics of migration. The proposed analysis might be considered as a useful reference for the development of public policies at the local level.